ANALISIS RASIO LIKUIDITAS PADA PT. MELATI MAKASSAR - M. Ihsan Malik (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2015)
This study aims to determine the financial performance. Jasmine Makassar in terms of liquidity ratio approach. The method of analysis used in this study is the approach Liquidity Ratio In PT.Melati Makassar. The results of the analysis of liquidity companies from 2008 to 2010, in general it can be said that the company's performance is not good enough. It can be seen from the fluctuation of the Current Ratio, Quick Ratio and Cash Ratio achieved by the company. Perusahaanmenurun liquidity caused by short-term debt increased by greater than current assets. This is because most bank loans (loans) company matures in April of 2010